TERORISMUL ÎN AFRICA ORGANIZAȚII TERORISTE PE TERITORIUL AFRICII - Alina (c. Tianu) IOVAN (Intelligence și Cultura de Securitate)
Africa has become a haven for jihadist terrorist organisations that run covers the whole range from local groups fighting to avenge political and economic grievances to splinter groups affiliated with the Islamic State in Iraq and Syria (ISIS) or al-Qaeda. Jihadist groups that have moved out of Syria and into the Sahel region or Africa after ISIS was defeated have only increased the terrorist threat in the region. Terrorists and violent extremists, including Da'esh, al-Qa'ida and their affiliates, have exploited instability and conflict to increase their activities and escalate attacks across the African continent. The vast Sahel region has become home to some of the most active and deadly terrorist groups and it is essential to better understand the links between organised crime and terrorism. Nearly half of the world's victims of terrorism are African, and organised crime is increasingly widespread. In a hyper-connected world, the spread of terrorism in Africa is not just a concern for African Member States, but for all. Combating international terrorism requires effective multilateral efforts.